2020
DOI: 10.3389/fpsyt.2019.00996
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Osteopontin and Interferon Gamma Serum Levels and Increased Neutrophil-to-Lymphocyte Ratio Are Associated With the Severity of Symptoms in Schizophrenia

Abstract: Inflammation and immune dysregulation could contribute to the pathogenesis of schizophrenia. Osteopontin (OPN) is a cytokine-like glycoprotein involved in inflammation and in modulating immune responses, and it can also directly modify the cytokine expression and survival of microglia. Furthermore, elevated gene expression of OPN in first episode psychosis has recently been described, but to date OPN level has not been investigated in schizophrenia. Imbalance of T-helper subtypes could also represent a vulnera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…To further define the effective direction between MSCs and TCs, the migration capacity of MSCs was investigated in the co‐culture of MSCs with TCs under the condition of either MSCs OPN– or TCs OPN– or both. Figure 7G demonstrated that OPN contributed to the infiltration of MSCs, and OPN from activated TCs could influence MSCs even more, similar to the finding that external OPN increased survival, proliferation, migration, and differentiation of neural stem cells at a dose‐dependent pattern 29 . OPN from MSCs or TCs played a decisive role in dynamic proliferation and movement of MSCs (Figure 7H).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…To further define the effective direction between MSCs and TCs, the migration capacity of MSCs was investigated in the co‐culture of MSCs with TCs under the condition of either MSCs OPN– or TCs OPN– or both. Figure 7G demonstrated that OPN contributed to the infiltration of MSCs, and OPN from activated TCs could influence MSCs even more, similar to the finding that external OPN increased survival, proliferation, migration, and differentiation of neural stem cells at a dose‐dependent pattern 29 . OPN from MSCs or TCs played a decisive role in dynamic proliferation and movement of MSCs (Figure 7H).…”
Section: Resultssupporting
confidence: 73%
“…Figure 7G demonstrated that OPN contributed to the infiltration of MSCs, and OPN from activated TCs could influence MSCs even more, similar to the finding that external OPN increased survival, proliferation, migration, and differentiation of neural stem cells at a dose-dependent pattern. 29 OPN from MSCs or TCs played a decisive role in dynamic proliferation and movement of MSCs ( Figure 7H). OPN from TCs played more important role in support of MSCs proliferation, and activated TCs could maintain dynamic proliferations of MSCs OPN-, while MSC OPN+ proliferation was lower when co-cultured with TCs OPN- (Figure 7H1).…”
Section: Roles Of Opn In Mscs-tcs Communicationmentioning
confidence: 99%
“…Moreover, four of five studies found positive correlation between PANSS total score and neutrophil count or NLR. Of note, in the study that did not report correlation with PANSS (30), the patients had lower total symptoms burden than the patients in the other studies (21)(22)(23)26). This indicates that the neutrophil numbers and NLR may be a state marker for disease severity or disease phase in schizophrenic patients, rather than an effect of antipsychotics.…”
Section: Discussionmentioning
confidence: 86%
“…Six studies investigated the effect of antipsychotics on neutrophil numbers ( Table 3 ). Three studies had longitudinal measurements ( 25 , 26 , 31 ), the others were cross-sectional ( 21 , 24 , 27 ). One study included a comparison based on antipsychotic response ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation